2017
DOI: 10.3390/md15090264
|View full text |Cite
|
Sign up to set email alerts
|

Review on Molecular Mechanisms of Antifouling Compounds: An Update since 2012

Abstract: Better understanding of the mechanisms of antifouling compounds is recognized to be of high value in establishing sensitive biomarkers, allowing the targeted optimization of antifouling compounds and guaranteeing environmental safety. Despite vigorous efforts to find new antifouling compounds, information about the mechanisms of antifouling is still scarce. This review summarizes the progress into understanding the molecular mechanisms underlying antifouling activity since 2012. Non-toxic mechanisms aimed at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 100 publications
(122 reference statements)
0
24
0
Order By: Relevance
“…Subsequent reviews focused either on biofouling and commercially important species [11,25] or particular processes, like quorum sensing and its inhibition [16,22]. Molecular mechanisms of larval settlement and inhibition were recently reviewed as well [52][53][54][55]. The development of novel omic-methods (metagenomics, metabolomics, transcriptomics, proteomics) resulted in many new findings in larval settlement and attachment.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent reviews focused either on biofouling and commercially important species [11,25] or particular processes, like quorum sensing and its inhibition [16,22]. Molecular mechanisms of larval settlement and inhibition were recently reviewed as well [52][53][54][55]. The development of novel omic-methods (metagenomics, metabolomics, transcriptomics, proteomics) resulted in many new findings in larval settlement and attachment.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a xanthone isolated from a marine-derived fungus Aspergillus terreus was also found to be a potent antifoulant [15]. Nonetheless, little information on structure-antifouling activity relationship and ultimately on the mechanism of action of polyketide-related compounds, namely xanthones, is available [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on nanomaterials stabilized by quaternary alkyl ammonium salts demonstrated a controlled copper release when they are put in contact with aqueous solutions, thus exerting a marked inhibiting action against the growth of various copper-sensitive microorganisms [2,19,27,[34][35][36]. In this work, a systematic evaluation of copper release properties in aqueous solutions of composite films stabilized by BAC disinfectant agent was performed as a function of the CuNPs loading.…”
Section: Spectroscopic Characterizaztionmentioning
confidence: 98%